Experimental studies on fire for offshore structures and its limitations: A review - Imran, M. (Italian Association of Chemical Engineering - AIDIC, 2015)
In past few decades a wide range of major accidents were reported due to oil & gas operation in offshore industry. Among of them hydrocarbon fire is the most frequently reported thread to offshore industry. It is an extremely costly and nearly impossible to conduct an experimental study on full scale offshore facilities under fire. But in order to understand the behaviour of fire and physically failure mode of structural member it is important to conduct an experimental study. For this purpose several studies focused just to understanding the behaviour of fire under expected fire scenarios. On the other hand, to maintain structure stability various structural members were tested under fire. In this review relevant studies will be presented to highlight and discuss the main studies based on experimental setup. Also the limitations of experimental studies will be highlighted in order to proposed comparison of experiment versus simulation. Although, simulation is considered to be the most economical and effect technique for modelling consequences before actual construction. It is recommended to validate simulation results obtained from computational fluid dynamics or nonlinear structural analysis which depends on the modelling techniques. Copyright Â© 2015, AIDIC Servizi S.r.l.,.